2018
DOI: 10.1021/acs.organomet.8b00628
|View full text |Cite
|
Sign up to set email alerts
|

A Ligand Protonation Series in Aluminum(III) Complexes of Tridentate Bis(enol)amine Ligand

Abstract: A series of aluminum(III) complexes supported by the tridentate bis(enol)amine ligand (ONO, 1,1′-azanediylbis(3,3-dimethylbutan-2-one)) in two protonation states have been synthesized and characterized structurally. Reaction of AlCl 3 with singly deprotonated H 2 ONO − afforded pseudooctahedral [(H 2 ONO − ) 2 Al][AlCl 4 ] (1). AlCl 3 was also reacted with doubly deprotonated HONO 2− to afford the five-coordinate, pseudotrigonal bipyramidal complex (HONO 2− )AlCl(THF) (2). The reaction of complex 2 with HCl yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Coordinating solvents, such as THF, may also coordinate to the metal. An example here is the formation of five-coordinate ( dipp I 2 P 2– )­AlCl­(THF) and four-coordinate ( dipp I 2 P 2– )­AlCl; they are obtained from the same reaction performed in THF or Et 2 O, respectively. , When the group 13 ion is coordinatively saturated, as in octahedral complexes with tridentate ligands, then some kinetic stability toward strongly donating solvents, such MeCN and H 2 O, has been observed, but these are rare examples. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coordinating solvents, such as THF, may also coordinate to the metal. An example here is the formation of five-coordinate ( dipp I 2 P 2– )­AlCl­(THF) and four-coordinate ( dipp I 2 P 2– )­AlCl; they are obtained from the same reaction performed in THF or Et 2 O, respectively. , When the group 13 ion is coordinatively saturated, as in octahedral complexes with tridentate ligands, then some kinetic stability toward strongly donating solvents, such MeCN and H 2 O, has been observed, but these are rare examples. , …”
Section: Introductionmentioning
confidence: 99%
“… 34 A third common synthetic approach is where the starting ligand is already isolated in a reduced and protonated state: in that case, deprotonation by a base such as NaH or KH affords the alkali-metal ligand salt, which will react with MCl 3 . This deprotonation approach has been employed in the synthesis of bis(enol)amine, 35 and in the synthesis of Al complexes with an iminocatecholate pincer ligand, 36 as examples. The three approaches described in this section have been employed extensively across many examples.…”
Section: Introductionmentioning
confidence: 99%
“…For example, as reported by Takaya and Iwasawa, the Pd complex A , containing a pincer-type Al unit as a ligand (Figure ), is a catalyst in the hydrosilylation of CO 2 . The Berben group found that the Al complex B , bearing a tridentate bis­(imino)­pyridine ligand, activates O–H and N–H bonds and catalyzes the conversion of formic acid to H 2 and CO 2 . In addition, they also found that pincer-type Al­(III) species, ( Ph I 2 P 2– )­AlH, can also activate polar chemical bonds. Recently, Aldridge and Goicoechea and co-workers exploited a dimeric potassium Al complex and its derivatives ( C ), which display unprecedented reactivity toward inert chemical bonds and small molecules .…”
Section: Introductionmentioning
confidence: 99%